2017
DOI: 10.3892/or.2017.5614
|View full text |Cite
|
Sign up to set email alerts
|

MCM7 amplification and overexpression promote cell proliferation, colony formation and migration in esophageal squamous cell carcinoma by activating the AKT1/mTOR signaling pathway

Abstract: The roles and mechanisms of mini-chromosome maintenance complex component 7 (MCM7) amplification and overexpression in esophageal carcinogenesis were investigated. By analyzing the TCGA datasets, we found that MCM7 was amplified in approximately 12% of esophageal squamous cell carcinomas (ESCCs), and in more than 4% of head and neck squamous cell carcinomas and stomach carcinomas. Overexpression of MCM7 was further verified in three independent GEO datasets of esophageal cancer. Knockdown of MCM7 using two siR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 34 publications
(34 reference statements)
2
34
0
Order By: Relevance
“…Knockdown of MCM6 was related to a delay in S/G2-phase progression with downregulation of CDK2, CDK4, CyclinA, CyclinB1, CyclinD1, and CyclinE in HCC [86]. Silencing of MCM7 reduced cyclinD1, cyclinE2, and CDK2 [58], which triggered events in the G1 or G1/S phase. Another experiment indicated that MCM8 bound to cyclin D1 to active Rb protein phosphorylation by Cdk4, and the binding allowed the entry into the S phase [51].…”
Section: Effects Of Mcms In Cellular Signalingmentioning
confidence: 97%
See 2 more Smart Citations
“…Knockdown of MCM6 was related to a delay in S/G2-phase progression with downregulation of CDK2, CDK4, CyclinA, CyclinB1, CyclinD1, and CyclinE in HCC [86]. Silencing of MCM7 reduced cyclinD1, cyclinE2, and CDK2 [58], which triggered events in the G1 or G1/S phase. Another experiment indicated that MCM8 bound to cyclin D1 to active Rb protein phosphorylation by Cdk4, and the binding allowed the entry into the S phase [51].…”
Section: Effects Of Mcms In Cellular Signalingmentioning
confidence: 97%
“…AKT is a serine/threonine kinase involved in the regulation of cell metabolism, proliferation, and survival. Silencing of MCM7 inhibited the phosphorylation of AKT1 and mTOR in both esophageal cancer cell lines, suggesting that MCM7 might promote cancer development and poor survival outcomes via activating the AKT1/mTOR signaling pathway [58]. Implicated genes and pathways in lymphoblastic lymphoma of MCM2-deficient mice include Pten, Tcfe2a, Mbd3, Setd1b, and Notch signaling pathway [36].…”
Section: Effects Of Mcms In Cellular Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is still lack of previous studies on the relationship between MCM7 and CRC. Though, many studies have shown that MCM7 proteins are involved in tumorigenesis [10]. MCM7 regulated the proliferation and migration of esophageal squamous cell carcinoma cells by activating the AKT1/mTOR pathway [11].…”
Section: Discussionmentioning
confidence: 99%
“…The minichromosome maintenance (MCM) complex is composed of six highly conservative MCM proteins, named MCM2-7(small body maintenance complex component 2-7), which is necessary to initiate DNA replication. MCM is a marker associated with proliferation of several types of cancer [6,10]. MCM2-7 forms the pre-replication complex (pre-RC), and then recognizes the origin recognition complex (ORC) before DNA replication [11].…”
Section: Introductionmentioning
confidence: 99%